2020
DOI: 10.1038/s41598-020-74041-9
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally friendly comprehensive hydrometallurgical method development for neodymium recovery from mixed rare earth aqueous solutions using organo-phosphorus derivatives

Abstract: Rare earth elements (REEs) have obtained a greatest significant in human lives owing to their important roles in various high technology applications. The present method development was deal technology important REEs such as neodymium, terbium and dysprosium, selective extraction with possible separation and recovery studies, successfully. The chloride mediated mixed aqueous solution containing 1500 mg/L each of REEs such as Nd, Tb and Dy was subjected at selective separation of Nd from other associated REEs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…These aspects, as well as favorable power-to-operate versus reactor-size scaling, make CLiRs an interesting alternative to the traditional hydrometallurgical methods and potentially applicable to separations of other valuable metals. [65][66][67][68]…”
Section: Discussionmentioning
confidence: 99%
“…These aspects, as well as favorable power-to-operate versus reactor-size scaling, make CLiRs an interesting alternative to the traditional hydrometallurgical methods and potentially applicable to separations of other valuable metals. [65][66][67][68]…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that HDEHP was successfully impregnated in SiPS. However, due to the strong absorption of SiO2, the characteristic peaks of P=O and P-O were covered by SiO2, which were reported locating at 1230 cm − 1 and 1030 cm − 1 , respectively [39,40]. The presence of P was finally determined using the XPS spectrum, as shown in Fig.…”
Section: Characterizationmentioning
confidence: 99%
“…The selectivity coefficient (S Nd/M ) was defined as the ratio of the distribution coefficient between Nd(III) and other metals eq 17. 53 S K (17) where K d (L/g) is the distribution coefficient of the selected metal ion between the adsorbent and the solution; C e (mmol/ L) and q e (mmol/g) are the concentration and adsorption capacities of the metal ion at the equilibrium.…”
Section: Ion Exchangementioning
confidence: 99%
“…There are several methods to separate and purify these ions, including classical hydrometallurgical processes (leaching, chemical precipitation, and solvent extraction), ion exchange, and adsorption . Leaching followed by the extraction of Nd has been proposed by several authors using alternative solvents. However, despite the high recovery of REM, solvent extraction is a high-cost and complex process that generates large volumes of waste . Adsorption, in turn, has stood out for its simplicity, high efficiency, capacity to concentrate, and desorb (recovery) the adsorbate from diluted solutions. , One of the determining factors for the overall adsorption efficiency is the type of the adsorbent matrix applied.…”
Section: Introductionmentioning
confidence: 99%